Analisis Citraan Kumpulan Puisi Surat Kopi Karya Joko Pinurbo - Kusmadi Sitohang; Dzikrina Rahmah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This study aims to analyze the imagery of Joko Pinurbo's collection of Surat Kopi poetry. This type of research is a qualitative research using descriptive analysis method. The data sources in this study were 10 poetry titles contained in Joko Pinurbo's collection of Surat Kopi poems. Data collection techniques were carried out through documentation studies. Data analysis techniques were carried out through descriptive analysis. The results of this study, namely the imagery contained in the 10 poetry titles in the poetry ontology of Joko Pinurbo's Surat Kopi are 3 imagery, namely visual, auditory, and motion imagery. From all these findings, it can be concluded that the most dominant element of imagery in this poem is visual imagery.